2003
DOI: 10.1083/jcb.200302084
|View full text |Cite
|
Sign up to set email alerts
|

Bax and Bak can localize to the endoplasmic reticulum to initiate apoptosis

Abstract: Bax and Bak play a redundant but essential role in apoptosis initiated by the mitochondrial release of apoptogenic factors. In addition to their presence at the mitochondrial outer membrane, Bax and Bak can also localize to the ER. Agents that initiate ER stress responses can induce conformational changes and oligomerization of Bax on the ER as well as on mitochondria. In wild-type cells, this is associated with caspase 12 cleavage that is abolished in bax − / − bak − / − cells. In bax − / − bak − / − cells, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
455
1
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(488 citation statements)
references
References 49 publications
22
455
1
10
Order By: Relevance
“…Edelfosine did not upregulate Grp78/BiP (Figure 2b), a major ER chaperone that binds Ca 2 þ and promotes tumor proliferation, survival, metastasis and resistance to a wide variety of therapies (Li and Lee, 2006). ER stress has been shown to induce activation of Bax (Zong et al, 2003), and we found Bax activation in response to edelfosine treatment in pancreatic cancer cells, by using an anti-Bax monoclonal antibody that recognized the active form of Bax (Figure 2b). Previous studies have shown that ASK1-mediated JNK activation is crucial for ER-induced apoptosis (Nishitoh et al, 2002).…”
Section: Induction Of Apoptosis By Edelfosine and Other Alps In Humanmentioning
confidence: 86%
“…Edelfosine did not upregulate Grp78/BiP (Figure 2b), a major ER chaperone that binds Ca 2 þ and promotes tumor proliferation, survival, metastasis and resistance to a wide variety of therapies (Li and Lee, 2006). ER stress has been shown to induce activation of Bax (Zong et al, 2003), and we found Bax activation in response to edelfosine treatment in pancreatic cancer cells, by using an anti-Bax monoclonal antibody that recognized the active form of Bax (Figure 2b). Previous studies have shown that ASK1-mediated JNK activation is crucial for ER-induced apoptosis (Nishitoh et al, 2002).…”
Section: Induction Of Apoptosis By Edelfosine and Other Alps In Humanmentioning
confidence: 86%
“…It remains to analyze the molecular mechanisms by which TOM22 (and, possibly, other components of the TOM complex) is involved in the apoptotic outer membrane permeabilization. Finally, since Bax also localize to the endoplasmic reticulum to initiate apoptosis, 35 the mechanism of interaction of Bax with this organelle is still to be determined and in particular its relationship with the organelle import apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ratio of Bax and Bak to Bcl-2 appears to be a key determinant of the levels of Ca 2 þ in the ER, as inferred from earlier studies. 93,97 In cells lacking Bax and Bak, uninhibited Bcl-2 leads to IP3R-1 hyperphosphorylation, enhanced ER Ca 2 þ release, and decreased steadystate ER Ca 2 þ stores. 94 Finally, Bid, Bik, and Bim, the upstream regulators of these Bcl-2 family members, are also influenced by proximal signals including ER stress.…”
Section: Gangliosides As Propagators Of the Er Stress-and Mitochondrimentioning
confidence: 99%